PENGARUH PENAMBAHAN ABU LIMBAH BATU BARA TERHADAP KARAKTERISTIK PASIR SEBAGAI LAPISAN PONDASI JALAN - Putra, Tjok. Gde Suwarsa; Ardana, Made Dodiek Wirya; Adi, Kadek Satria (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 24, No. 1, Januari 2020, 2021)
The road base course layer is a part of highway pavement lied between the road surface layer and the subgrade. The base course layer on the flexible pavement spreads the load of the vehicle so that the stresses on the subgrade will not exceed the allowable stress that can cause excessive deformation. The base course layer has a specifications in determining the material to be used, both grain size, physical properties, and carrying capacity values ??(The California Bearing Ratio, CBR) where the CBR value is the carrying capacity of the base course layer and can also be used as a reference in determining the thickness of the base course layer. The dominant material used in the base course layer is sand/gravel. Sand/gravel has a larger grain size than clay. The incompatibility of the material used with the specifications used for the base course layer, especially for grain grading problems that lack fine grains can be overcome by adding a certain material that is useful for completing less granular gradations, and can increase the carrying capacity (CBR) of the foundation layer road. In this study, the material that will be added to material that does not conform to the specifications of the base course layer is coal waste ash, where the addition will be sought for the percentage of coal ash waste mixture with material that does not fit the specifications of the best road foundation for entry specifications of road foundation gradation. The results of this study found the percentage of addition of coal waste ash to the soil material tested most included in the specifications of the base course layer gradation of 13% of the dry weight of the soil. In addition, the addition of coal waste ash produces a relative density of soil and soil density increases, therefore the CBR value of the soil also increases. The initial CBR value was 62% and the value increased to 94% after the coal waste ash was added to the base course material.